Some properties of two dimensional extended repulsive Hubbard model with intersite magnetic interactions - a Monte Carlo study - Murawski, Szymon; Kapcia, Konrad Jerzy; Pawłowski, Grzegorz; Robaszkiewicz, Stanisław (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, PL-02-668 Warsaw, Poland, 2014)
In this paper the two dimensional extended Hubbard model with intersite magnetic Ising-like interaction in the atomic limit is analyzed by means of the classical Monte Carlo method in the grand canonical ensemble. Such an effective simple model could describe behavior of insulating (anti)ferromagnets. In the model considered the Coulomb interaction (U) is on-site and the magnetic interactions in z-direction (J>0, antiferromagnetic) are restricted to nearest-neighbors. Simulations of the model have been performed on a square lattice consisting of N=LxL=400 sites (L=20) in order to obtain the full phase diagram for U/(4J)=1. Results obtained for on-site repulsion (U>0) show that, apart from homogeneous non-ordered (NO) and ordered magnetic (antiferromagnetic, AF) phases, there is also a region of phase separation (PS: AF/NO) occurrence. We present a phase diagram as well as some thermodynamic properties of the model for the case of U/(4J)=1 (and arbitrary chemical potential and arbitrary electron concentration). The AF-NO transition can be second-order as well as first-order and the tricritical point occurs on the diagram.
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A. The Version of Record is available online at http://dx.doi.org/10.12693/APhysPolA.126.A-110
Keywords: extended Hubbard model; atomic limit; phase separation; magnetism; phase diagrams; mean-field; Monte Carlo simulations